A Critical Portfolio: Being Chiefly Reports on New Music and Opera (1987-88) by a Critic Living in Hamilton, Ontario - Gasser, Richard Alan (My University, 1988)
The critical portfolio here collected was written under the guidance of Mr. William Littler, music critic of the Toronto Star. ][t is primarily an idiosyncratic account of the new music concerts and opera productions in the Toronto and Hamilton area between June, 1987 and June, 1988. Canadian composers, performers and performings organizations are mentioned prominently, though significant concerts and operas from elsewhere lend breadth and depth to the coverage.
In an introductory essay, the thorny matter of using words to write about music is dealt with obliquely, through a discussion of the organization of the separate reports into a portfolio. The overall form of the portfolio is a literary one which alludes to traditional symphonic forms.
A short statement of the author's critical predilections serves as the critical creed in which these separate reports have a common origin. The introduction also lists the publications in which the some of the critiques first appeared. A summary of the editorial practices of the different publications explains the outside influences on the writing included in this portfolio.
Keywords: Music; Music